Health insurance coverage among women in Indonesia's major cities: A multilevel analysis. Issue 3 (4th March 2017) - Christiani, Yodi; Byles, Julie E.; Tavener, Meredith; Dugdale, Paul
ABSTRACT: We examined women's access to health insurance in Indonesia. We analyzed IFLS-4 data of 1, 400 adult women residing in four major cities. Among this population, the health insurance coverage was 24%. Women who were older, involved in paid work, and with higher education had greater access to health insurance ( p < . 05). We also found there were disparities in the probability of having health insurance across community levels (Median Odds Ratios = 3.40). Given the importance of health insurance for women's health, strategies should be developed to expand health insurance coverage among women in Indonesia, including the disparities across community levels. Such problems might also be encountered in other developing countries with low health insurance coverage.